2015
DOI: 10.3390/ijerph120201156
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Underweight and Overweight in South African Children: Are We Winning or Losing the Battle? A Systematic Review

Abstract: Underweight and overweight are adverse effects of malnutrition and both are associated with negative health consequences in children and adolescents. In South Africa, the burden of economic and social disparity coexists with malnutrition in children. The purpose of this study was to review available South African studies regarding the comprehensive summary of prevalence of underweight and overweight and evaluates government policies in addressing undernutrition and overnutrition in South African children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 36 publications
5
39
0
Order By: Relevance
“…In addition, urban children showed higher anthropometric measures compared to rural children. This is in agreement with a study conducted by Monyeki and colleagues [29] who reported that the prevalence of obesity among South African children was higher in urban (6.1%) than in rural (3.7%) children aged 0-18 years old. The high prevalence of obesity in urban children could be as a result of the availability of inexpensive processed and lower nutrient foods in urban areas as it has been reported by McKersie and Baard [26] to be linked with the incidence of childhood obesity.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, urban children showed higher anthropometric measures compared to rural children. This is in agreement with a study conducted by Monyeki and colleagues [29] who reported that the prevalence of obesity among South African children was higher in urban (6.1%) than in rural (3.7%) children aged 0-18 years old. The high prevalence of obesity in urban children could be as a result of the availability of inexpensive processed and lower nutrient foods in urban areas as it has been reported by McKersie and Baard [26] to be linked with the incidence of childhood obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Rather, the logical extension of these ideas would suggest that these efforts should carefully consider the unique (and possibly different) needs of the children being targeted. To illustrate, lowand middle-income countries including South Africa, 58 India, 59 and Brazil 60 face a double burden of over-and under-nutrition. These burdens can occur within the same community, as both under-and over-nutrition are associated with social and economic inequalities.…”
Section: Physical Activity and Malnutritionmentioning
confidence: 99%
“…These burdens can occur within the same community, as both under-and over-nutrition are associated with social and economic inequalities. 58,61 In settings such as these, it is therefore essential to promote physical activity as a means of preventing and/or managing overweight and obesity in early childhood and later life. At the same time, it is also important to understand the potential physiological consequences of promoting dramatic energy expenditure increases with early childhood populations in which under-nutrition is more prevalent.…”
Section: Physical Activity and Malnutritionmentioning
confidence: 99%
“…14 Among these few in SSA, not all assessed childhood growth for more than a year and were mostly conducted in only five African countries. [15][16][17][18][19][20] Urban residence has been identified as a risk factor for intrauterine and postnatal malnutrition in Africa, the continent with the highest urbanisation rate in the world. 21,22 A number of the existing longitudinal data collection systems on the continent are located in rural areas with relatively homogenous populations, which are unsuitable for addressing the complex interaction of sociodemographic and economic factors with growth faltering and urbanisation.…”
Section: Introductionmentioning
confidence: 99%